ESTIMATING THE MAXIMUM SYNCHRONIZATION DRIFT IN SELF ORGANIZING WIRELESS SENSOR NETWORKS - Pella, S. I. (Jurnal Media Elektro, 2017)
The nodes in self-organizing wireless sensor networks (WSNs) do not have means for synchronizing their clock with a global reference. To maintain a local synchronization, the nodes to periodically propagate a small control packet called SYNC. The propagation delay suffered by the packet caused the synchronization drift in the network, which is proportional to the length of the propagation path. This paper aims to investigate ways to calculating the maximum synchronization drift that could happen in a network. We propose a method to theoretically calculate the upper bound of the maximum schedule drift in a network, which serve as the worst case scenario. We then run simulations to see the effect of network density and nodeâs transmission range to the maximum synchronization in the network for various network sizes. Finally, we proposeÂ  a way to estimate the maximum synchronization drift in a dense network.